Akuntabilitas dalam Kebijakan Perlindungan Data Pribadi di Indonesia: Belajar dari Korea Selatan dan Singapura - Badriah, Lailatul; Indiahono, Dwiyanto; Sukarso (Research and Development Agency Ministry of Home Affairs, 2024)
This article examines the value of accountability in personal data protection policies in South Korea, Singapore and Indonesia with the main objective of providing a framework for innovation for Indonesia. This research emphasizes the comparison of innovative strategies in five aspects: defining protected personal data, mechanisms for collecting and transferring personal data, innovative mechanisms for reporting data breaches, and mechanisms for providing sanctions and compensation for data breaches. Using a qualitative method and content analysis approach to South Korea’s Personal Information Protection Act (PIPA), Singapore’s Personal Data Protection Act (PDPA), and Indonesia’s Law No. 27 of 2022 on Personal Data Protection, the findings underscore the importance of accountable policy innovation to ensure the protection of individual rights and empower the institution of personal data protection authorities. The main implications are for Indonesia to immediately implement Law No. 27 of 2022 on Personal Data Protection, establish a centralized data protection authority, and encourage Public-Private Partnerships to improve accountability in personal data protection.